Development of a new expert system for diagnosing marine diesel engines based on real-time diagnostic parameters - Gharib, Hla (Strojniški vestnik, 2022)
Implementing adequate diagnostic strategies for marine engines offers a good possibility to focus on the early recognition of potentialproblems and prevent catastrophic and costly consequences. The successful and increasing application of diagnostic systems and devices for machines depends significantly on the precision of the diagnostic approaches. This research aims to develop an improved diagnosis expert system for determining the real-time technical condition of marine diesel engines. The adequate selection of the diagnostic parameters is crucial in detecting early-stage defects and failures since each parameter responds to the changes in structural parameters of the engine in different modes and degrees. This result provides valuable information on the accurate location of the fault and describes the relationship between operational and structural parameters. Firstly, this article introduces the relevant literature relating to the selection of the diagnostic parameters for marine engines and their subsystems through different statistical methods. The next part contains the description of marine diesel engine subsystems and the selected marine diesel engine’s diagnostic parameters. After that, a newly developed expert system for diagnosing marine diesel engines’ technical conditions is introduced. Finally, a case study of the operation of the developed diagnostic system is presented. The main contribution of the article is the introduction of the newly developed diagnosis expert system, which can be offered to inexperienced users on ships to effectively manage abnormal situations. Furthermore, this diagnostic tool can be applied to the engines’ subsystems to improve the reliability and efficiency of the marine diesel engines’ operation and maintenance.
Keywords: case study; diagnostic parameters; diagnostični parametri; maintenance; marine engines; motorji za plovila; newly developed diagnosis expert system; nov diagnostični ekspertni sistem; študija primera; vzdrževanje